Teaching Note—Theory as a Pedagogical Tool: A Three-Question Framework for Course Design. - Ager, Mary Elizabeth (Journal of Social Work Education)
Designing or redesigning a course can bring many challenges to the social work educator in the 21st century. The aim of this teaching note is to offer a novel course design framework that consists of three theory-based questions. It is written in a first-person narrative style that highlights the framework's development and case examples from more than a decade of teaching undergraduate, Master of Social Work, and doctoral-level courses in social work by the author. The three questions that form the structure of the framework are: "What is?," "Why is it that way?," and "How should it be instead?" The questions encompass the enormous range of descriptive, explanatory, and normative theories, respectively, of a given social phenomenon or social work intervention approach. A course designed in this way requires social work students to explore actively divergent points of view and engage in understanding and making the link between conceptualization, explanation, and intervention. This framework can also be used to design modules of courses, single lectures, or class sessions and can work across the social work curriculum, from practice and policy-based courses to advanced electives.